Toothpaste containing hydroxyapatite-silk fibroin oligopeptide mineralization material and preparation method thereof
By performing specific process treatment of silk fibroin and remineralizing with hydroxyapatite, a toothpaste for efficient restoration of enamel was developed, which solved the toxic side effects of fluoride treatment in the prior art and the limited remineralization of hydroxyapatite materials, and achieved the purpose of improving the hardness of enamel and anti-carious effects.
Patent Information
- Application Number
- CN202411970413.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, when fluoride is used for enamel remineralization treatment, it is easy to cause toxic side effects such as fluorosis, skeletal fluorosis, and acute fluorosis, and the use of hydroxyapatite materials alone has limited remineralization effect on enamel caries lesions.
By performing enzymatic, alkaline and oxidative degradation of silk fibroprotein, silk fibroprotein oligomeric peptides are prepared and remineralized with hydroxyapatite, a toothpaste that can efficiently repair tooth enamel is developed.
This toothpaste can effectively repair enamel, increase the Vickers hardness of the enamel block after remineralization, reduce the degree of enamel demineralization, reduce the plaque index of patients with chalky plaques in enamel demineralization, achieve the effect of preventing caries, and avoid the toxic side effects of fluoride.
Smart Images

Figure BDA0005219382660000221 
Figure BDA0005219382660000231 
Figure BDA0005219382660000241
Abstract
Description
Technical Field
[0001] The invention belongs to the field of application of natural products, and particularly relates to a toothpaste containing a hydroxyapatite-silk fibroin oligopeptide mineralized material and a preparation method thereof. Background Art
[0002] Mature human tooth enamel is a highly mineralized tissue, mainly composed of inorganic minerals, which are mainly composed of hydroxyapatite, which is arranged in parallel and perpendicular to the surface of the enamel, forming a hydroxyapatite prism structure. Under normal circumstances, hydroxyapatite is a relatively stable structure, and demineralization and remineralization are in a dynamic equilibrium. However, when this balance is disrupted, the enamel will be demineralized and early caries will be generated.
[0003] In clinical practice, fluoride is mainly used for remineralization treatment of enamel caries. However, excessive fluoride can lead to toxic side effects such as dental fluorosis, skeletal fluorosis, and acute fluorosis. Bionic enamel remineralization is a new type of early caries treatment method. Hydroxyapatite has a similar mineral content to that of tooth hard tissue, and has high bioactivity and biocompatibility. The use of hydroxyapatite material alone for enamel remineralization mainly utilizes its nano-size effect to fill the demineralized areas, so the remineralization effect on enamel caries is limited. Therefore, it is particularly critical and important to develop a high-quality toothpaste that can efficiently repair enamel. Summary of the invention
[0004] The purpose of the present invention is to address the toxic side effects such as dental fluorosis, skeletal fluorosis, and acute fluorosis caused by the use of fluoride for remineralization treatment in the prior art, thereby developing a toothpaste that can efficiently repair tooth enamel based on the silk fibroin oligopeptide obtained after oxidative degradation and other processing, and remineralizing it with hydroxyapatite.
[0005] To achieve the above object, the present invention is achieved by the following means:
[0006] The first aspect of the present invention provides a method for preparing a hydroxyapatite-silk fibroin oligopeptide mineralized material, comprising the following steps:
[0007] (1) preparing a silk fibroin solution from silkworm cocoons, and adjusting the concentration of the silk fibroin to 10-100 mg / mL;
[0008] (2) adding neutral protease for the first enzymatic hydrolysis; then adding β-glucanase for the second enzymatic hydrolysis;
[0009] (3) adding NaOH to adjust the pH to alkaline, performing alkaline hydrolysis under shaking conditions, and then adjusting the pH to neutral;
[0010] (4) adding an oxidant to carry out an oxidative degradation reaction under stirring; then adding a reducing agent to continue the stirring reaction;
[0011] (5) ultrafiltration of the reaction product to obtain a silk fibroin oligopeptide solution, and freeze-drying to obtain a silk fibroin oligopeptide;
[0012] (6) The silk fibroin oligopeptide obtained in step (5) is mixed with hydroxyapatite and dissolved in a saturated calcium nitrate solution, and a sodium phosphate solution is added dropwise under stirring to carry out a mineralization reaction; after the mineralization reaction is completed, the pH is adjusted to neutral, the precipitate is collected by centrifugation, and the precipitate is dried and ultrafinely ground and sieved to obtain the product.
[0013] Preferably, the silk fibroin solution in step (1) is prepared by the following steps:
[0014] (1.1) Cutting the cocoons into pieces, adding them into a sodium carbonate solution and boiling them, then soaking and washing them with water; repeating the boiling and washing process 1-5 times, and drying them to obtain degummed silk;
[0015] (1.2) dissolving the degummed silk in a lithium bromide solution, filtering to remove large particles of impurities, and then centrifuging to obtain a crude silk fibroin extract;
[0016] (1.3) The crude silk fibroin extract is transferred to a dialysis bag for dialysis; when the water level in the dialysis bag no longer changes, the dialysis bag containing the crude silk fibroin extract is placed in a polyethylene glycol solution for concentration to obtain the product.
[0017] Preferably, the concentration of the sodium carbonate solution in step (1.1) is 0.1-1.0 wt %; more preferably, the concentration of the sodium carbonate solution is 0.5 wt %.
[0018] Preferably, in step (1.1), the boiling time is 30-90 min, the washing time is 5-20 min, and the boiling and washing processes are repeated 2-4 times; more preferably, the boiling time is 60 min, the washing time is 10 min, and the boiling and washing processes are repeated 3 times.
[0019] Preferably, the concentration of the lithium bromide solution in step (1.2) is 5-15 mol / L, and the temperature of the lithium bromide solution is 40-70°C; more preferably, the concentration of the lithium bromide solution is 9.5 mol / L, and the temperature of the lithium bromide solution is 60°C.
[0020] Preferably, in step (1.2), the mass ratio of the degummed silk to the lithium bromide solution is 1:3-10; more preferably, the mass ratio of the degummed silk to the lithium bromide solution is 1:6.
[0021] Preferably, the centrifugal speed in step (1.2) is 5000-15000 rpm, and the time is 5-15 min; more preferably, the centrifugal speed is 9000 rpm, and the time is 10 min.
[0022] Preferably, the relative molecular mass retained by the dialysis bag in step (1.3) is 5-15 kDa, and the dialysis time is 1-3 days; more preferably, the relative molecular mass retained by the dialysis bag is 10 kDa, and the dialysis time is 2 days.
[0023] Preferably, the concentration of the polyethylene glycol solution in step (1.3) is 5-20%, and the concentration time is 5-20 h; more preferably, the concentration of the polyethylene glycol solution is 10%, and the concentration time is 12 h.
[0024] Preferably, the amount of the neutral protease used in step (2) is 2-20% of the mass of the silk fibroin protein; the amount of the β-glucanase used is 1-5% of the mass of the silk fibroin protein.
[0025] Preferably, the temperature of the first enzymatic hydrolysis in step (2) is 30-50°C, and the time is 30-90 min; more preferably, the temperature of the first enzymatic hydrolysis is 35-45°C, and the time is 45-75 min.
[0026] Preferably, the temperature of the second enzymolysis in step (2) is 40-60°C, and the time is 10-60 min; more preferably, the temperature of the second enzymolysis is 45-55°C, and the time is 20-40 min.
[0027] Preferably, in step (3), the pH is adjusted to 8.0-11.0; more preferably, the pH is adjusted to 8.5-9.5.
[0028] Preferably, the concentration of NaOH in step (3) is 0.5-3 mol / L; more preferably, the concentration of NaOH is 1 mol / L.
[0029] Preferably, in step (3), the oscillation speed is 30-100 rpm, the alkaline hydrolysis temperature is 40-60°C, and the time is 1-10 h; more preferably, the oscillation speed is 50-70 rpm, the alkaline hydrolysis temperature is 50-55°C, and the time is 3-8 h.
[0030] Preferably, the oxidant in step (4) is selected from hydrogen peroxide; more preferably, the oxidant is selected from hydrogen peroxide with a concentration of 2.5 mmol / L.
[0031] Preferably, the volume ratio of the oxidant to the silk fibroin solution is 0.0001-0.001:1.
[0032] Preferably, the temperature of the oxidative degradation reaction in step (4) is 30-60°C, and the time is 1-20 min; more preferably, the temperature of the oxidative degradation reaction is 40-50°C, and the time is 5-15 min.
[0033] Preferably, the reducing agent in step (4) is selected from vitamin C; more preferably, the reducing agent is selected from vitamin C with a concentration of 10 mmol / L.
[0034] Preferably, the volume ratio of the reducing agent to the silk fibroin solution is 0.0001-0.0005:1.
[0035] Preferably, the stirring reaction in step (4) is carried out at a temperature of 30-60°C and for a time of 10-60 min; more preferably, the stirring reaction is carried out at a temperature of 35-45°C and for a time of 20-40 min.
[0036] Preferably, the ultrafiltration in step (5) is as follows: the product after the reaction is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa, and the effluent is taken; then the product is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution.
[0037] Preferably, in step (6), the mass ratio of the silk fibroin oligopeptide to hydroxyapatite is 1:1-3; more preferably, the mass ratio of the silk fibroin oligopeptide to hydroxyapatite is 1:1.2-2.0.
[0038] Preferably, in step (6), the mass volume ratio of the silk fibroin oligopeptide to the saturated calcium nitrate solution is 0.01-0.1:1; more preferably, the mass volume ratio of the silk fibroin oligopeptide to the saturated calcium nitrate solution is 0.02-0.06:1.
[0039] It should be understood that, unless otherwise specified, the "mass-to-volume ratio" in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the mass of the solid substance (in g) to the liquid volume (in mL). For example, when the "mass-to-volume ratio of silk fibroin oligopeptide to saturated calcium nitrate solution is 0.05:1", if the amount of silk fibroin oligopeptide added is 5 g, the amount of saturated calcium nitrate solution added is 100 mL.
[0040] Preferably, in step (6), the mass ratio of the silk fibroin oligopeptide to the sodium phosphate in the sodium phosphate solution is 0.5-2:1; more preferably, the mass ratio of the silk fibroin oligopeptide to the sodium phosphate in the sodium phosphate solution is 1-1.5:1.
[0041] Preferably, the temperature of the mineralization reaction in step (6) is 30-40°C, and the time is 24-96h; more preferably, the temperature of the mineralization reaction is 35-38°C, and the time is 36-72h.
[0042] The second aspect of the present invention provides a hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method.
[0043] The third aspect of the present invention provides the use of the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method in the preparation of toothpaste.
[0044] The fourth aspect of the present invention provides a toothpaste comprising the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the above preparation method, and auxiliary materials.
[0045] Preferably, the auxiliary materials include one or more of silicon dioxide, sorbitol, propylene glycol, xylitol, sodium carboxymethyl cellulose, sodium lauryl sulfate, carrageenan, sodium benzoate and water.
[0046] Preferably, the toothpaste comprises the following ingredients in percentage by mass:
[0047] 5-15% hydroxyapatite-silk fibroin oligopeptide mineralized material, 15-30% silicon dioxide, 5-15% sorbitol, 1-5% propylene glycol, 1-5% xylitol, 1-3% sodium carboxymethyl cellulose, 0.5-3% sodium dodecyl sulfate, 0.5-2% carrageenan, 0.05-0.5% sodium benzoate, and the balance is water; the total mass percentage of each component is 100%.
[0048] In the inorganic-organic biomineralization process of tooth enamel mediated by ameloblasts, protein components play a key role. The remineralization process of protein and hydroxyapatite can give hydroxyapatite amazing structural mechanical properties. The reason is that protein participates in the directional growth process of hydroxyapatite crystals during the mineralization process. This hydroxyapatite-protein remineralization material can be adsorbed on the surface of corroded enamel crystals and directional arrange bundles of enamel crystal layers to achieve the effect of repairing tooth enamel.
[0049] Fibroin is a natural polymer extracted from silk fiber, with excellent biocompatibility. However, due to the high molecular weight of fibroin, specific surface area and dispersibility are poor. To this end, the present invention has been studied in large quantities, and has been subjected to enzymolysis, alkaline hydrolysis and oxidative degradation of specific processes to fibroin, which can significantly improve its specific surface area and dispersibility, and is convenient to be evenly dispersed in an aqueous solution, which helps to better remineralize with hydroxyapatite. Subsequently, remineralization treatment is carried out with hydroxyapatite to obtain a mineralized material, and toothpaste is prepared with this, which can improve the promotion of enamel remineralization, improve the Vickers hardness of enamel blocks after remineralization, reduce the degree of enamel demineralization, reduce the plaque index of patients with enamel demineralization chalky spots, and then achieve the effect of preventing caries. In addition, the present invention uses natural products such as silkworm cocoons as active ingredients, has good safety, low cost, and has great market prospects and social significance. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] Example 1
[0052] A hydroxyapatite-silk fibroin oligopeptide mineralized material, the preparation method of which comprises the following steps:
[0053] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0054] (2) Take 1L of silk fibroin solution, add 2g of neutral protease (10000U / g) and enzymatically hydrolyze at 40℃ for 1h; then add 2.5g of β-glucanase (3000U / g) and enzymatically hydrolyze at 50℃ for 0.5h.
[0055] (3) 1 mol / L NaOH was added to adjust the pH to 9.0, and the mixture was oscillated at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0056] (4) Add 0.5 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 45°C with stirring for 10 min; then add 0.3 mL of 10 mmol / L vitamin C and carry out stirring reaction at 40°C for 0.5 h.
[0057] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0058] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0059] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% hydroxyapatite-silk fibroin oligopeptide mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium dodecyl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0060] Example 2
[0061] A hydroxyapatite-silk fibroin oligopeptide mineralized material, the preparation method of which comprises the following steps:
[0062] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0063] (2) Take 1L of silk fibroin solution, add 4g of neutral protease (10000U / g) and hydrolyze at 35℃ for 75min; then add 1g of β-glucanase (3000U / g) and hydrolyze at 45℃ for 40min.
[0064] (3) 1 mol / L NaOH was added to adjust the pH to 9.5, and the mixture was oscillated at 70 rpm and 50°C for 3 h, and then the pH was adjusted to 7.0.
[0065] (4) Add 1 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 40°C with stirring for 15 minutes; then add 0.5 mL of 10 mmol / L vitamin C and carry out stirring reaction at 35°C for 40 minutes.
[0066] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0067] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0068] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% hydroxyapatite-silk fibroin oligopeptide mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium dodecyl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0069] Example 3
[0070] A hydroxyapatite-silk fibroin oligopeptide mineralized material, the preparation method of which comprises the following steps:
[0071] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0072] (2) Take 1L of silk fibroin solution, add 1g of neutral protease (10000U / g) and enzymatically hydrolyze at 45℃ for 45min; then add 0.5g of β-glucanase (3000U / g) and enzymatically hydrolyze at 55℃ for 20min.
[0073] (3) 1 mol / L NaOH was added to adjust the pH to 8.5, and the mixture was oscillated at 50 rpm and 55°C for 8 h, and then the pH was adjusted to 7.0.
[0074] (4) Add 0.2 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 50°C with stirring for 5 minutes; then add 0.1 mL of 10 mmol / L vitamin C and carry out stirring reaction at 45°C for 20 minutes.
[0075] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0076] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0077] Furthermore, the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared as above is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% hydroxyapatite-silk fibroin oligopeptide mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium dodecyl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0078] Comparative Example 1
[0079] A mineralized material, the preparation method of which comprises the following steps:
[0080] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0081] (2) Take 1 L of silk fibroin solution, add 2.5 g of β-glucanase (3000 U / g) and perform enzymatic hydrolysis at 50 °C for 0.5 h.
[0082] (3) 1 mol / L NaOH was added to adjust the pH to 9.0, and the mixture was oscillated at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0083] (4) Add 0.5 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 45°C with stirring for 10 min; then add 0.3 mL of 10 mmol / L vitamin C and carry out stirring reaction at 40°C for 0.5 h.
[0084] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0085] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0086] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following components in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0087] Comparative Example 2
[0088] A mineralized material, the preparation method of which comprises the following steps:
[0089] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0090] (2) Take 1 L of silk fibroin solution, add 2.5 g of β-glucanase (3000 U / g) and enzymatically hydrolyze at 50°C for 0.5 h; then add 2 g of neutral protease (10000 U / g) and enzymatically hydrolyze at 40°C for 1 h.
[0091] (3) 1 mol / L NaOH was added to adjust the pH to 9.0, and the mixture was oscillated at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0092] (4) Add 0.5 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 45°C with stirring for 10 min; then add 0.3 mL of 10 mmol / L vitamin C and carry out stirring reaction at 40°C for 0.5 h.
[0093] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0094] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0095] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0096] Comparative Example 3
[0097] A mineralized material, the preparation method of which comprises the following steps:
[0098] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0099] (2) Take 1L of silk fibroin solution, add 2g of neutral protease (10000U / g) and enzymatically hydrolyze at 40℃ for 1h; then add 2.5g of β-glucanase (3000U / g) and enzymatically hydrolyze at 50℃ for 0.5h.
[0100] (3) Add 0.5 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 45°C with stirring for 10 min; then add 0.3 mL of 10 mmol / L vitamin C and carry out stirring reaction at 40°C for 0.5 h.
[0101] (4) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0102] (5) 4 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0103] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0104] Comparative Example 4
[0105] A mineralized material, the preparation method of which comprises the following steps:
[0106] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0107] (2) 1 L of silk fibroin solution was added with 1 mol / L NaOH to adjust the pH to 9.0, and the solution was subjected to alkaline hydrolysis at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0108] (3) Add 2 g of neutral protease (10,000 U / g) and perform enzymatic hydrolysis at 40°C for 1 h; then add 2.5 g of β-glucanase (3,000 U / g) and perform enzymatic hydrolysis at 50°C for 0.5 h.
[0109] (4) Add 0.5 mL of 2.5 mmol / L hydrogen peroxide and carry out oxidative degradation reaction at 45°C with stirring for 10 min; then add 0.3 mL of 10 mmol / L vitamin C and carry out stirring reaction at 40°C for 0.5 h.
[0110] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0111] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0112] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0113] Comparative Example 5
[0114] A mineralized material, the preparation method of which comprises the following steps:
[0115] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0116] (2) Take 1L of silk fibroin solution, add 2g of neutral protease (10000U / g) and enzymatically hydrolyze at 40℃ for 1h; then add 2.5g of β-glucanase (3000U / g) and enzymatically hydrolyze at 50℃ for 0.5h.
[0117] (3) 1 mol / L NaOH was added to adjust the pH to 9.0, and the mixture was oscillated at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0118] (4) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0119] (5) 4 g of the silk fibroin oligopeptide obtained in step (4) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0120] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0121] Comparative Example 6
[0122] A mineralized material, the preparation method of which comprises the following steps:
[0123] (1) Select high-quality and clean silk cocoons, cut them into pieces, add them to a boiling 0.5wt% sodium carbonate solution, boil them for 60 minutes, and then soak and wash them with distilled water for 10 minutes; repeat the above boiling and washing process 3 times, and dry them to obtain degummed silk; dissolve the degummed silk in a 60°C, 9.5mol / L lithium bromide solution (the mass ratio of degummed silk to lithium bromide solution is 1:6), and after cooling to room temperature, use a filter to remove large particles of impurities, centrifuge at 9000rpm for 10 minutes to obtain a crude silk fibroin extract; transfer the crude silk fibroin extract to a dialysis bag with a cutoff relative molecular mass of 10kDa, and continue to dialyze with ultrapure water for 2 days until the water level in the dialysis bag no longer changes; further, place the dialysis bag containing the crude silk fibroin extract in a 10% polyethylene glycol solution for concentration for 12 hours to obtain a silk fibroin solution, and adjust the silk fibroin concentration to 50mg / mL.
[0124] (2) 1 L of silk fibroin solution was added with 0.5 mL of 2.5 mmol / L hydrogen peroxide and subjected to an oxidative degradation reaction at 45°C with stirring for 10 min; then 0.3 mL of 10 mmol / L vitamin C was added and subjected to a stirring reaction at 40°C for 0.5 h.
[0125] (3) Add 2 g of neutral protease (10,000 U / g) and perform enzymatic hydrolysis at 40°C for 1 h; then add 2.5 g of β-glucanase (3,000 U / g) and perform enzymatic hydrolysis at 50°C for 0.5 h.
[0126] (4) 1 mol / L NaOH was added to adjust the pH to 9.0, and the mixture was oscillated at 60 rpm and 55°C for 5 h, and then the pH was adjusted to 7.0.
[0127] (5) The supernatant of the reaction product is first separated by an ultrafiltration membrane with a molecular weight of 3 kDa to remove macromolecular substances, and the effluent is taken; then it is separated by an ultrafiltration membrane with a molecular weight of 0.5 kDa, and the retentate is taken to obtain a 0.5-3 kDa silk fibroin oligopeptide solution, which is then freeze-dried to obtain silk fibroin oligopeptide.
[0128] (6) 4 g of the silk fibroin oligopeptide obtained in step (5) was mixed with 6 g of hydroxyapatite and dissolved in 100 mL of saturated calcium nitrate solution. 10 mL of 2 mol / L sodium phosphate solution was added dropwise at 37° C. with stirring. The mixture was subjected to mineralization reaction at 37° C. for 48 h. After the mineralization reaction, the pH was adjusted to 7.0, the precipitate was collected by centrifugation, dried, and ultrafinely ground to pass through a 10,000 mesh sieve.
[0129] Furthermore, the prepared mineralized material is used to prepare toothpaste according to the conventional method in the art, and the toothpaste comprises the following ingredients in percentage by weight: 10% mineralized material, 20% silicon dioxide, 10% sorbitol, 2% propylene glycol, 2% xylitol, 2% sodium carboxymethyl cellulose, 1% sodium lauryl sulfate, 1% carrageenan, 0.1% sodium benzoate, and the balance is water.
[0130] Verification Example 1
[0131] The mineralized materials prepared in the examples and comparative examples were respectively taken to study their effects on the remineralization of tooth enamel.
[0132] The steps of preparing the enamel sample are as follows: fresh bovine teeth are taken, soft tissues are removed, crowns and roots are separated with a hard tissue slicer, the crown surface is polished into a smooth plane with a grinder and polisher, ultrasonic cleaning is performed for 30 minutes, deionized water is rinsed, placed in a 0.9% sodium chloride solution, and stored at 4°C for use. The enamel samples are observed under a microscope, and intact enamel without cracks, caries, or fluoride spots is selected, rinsed with deionized water, and dried, and randomly divided into a negative group (without demineralization treatment), a demineralization group, an embodiment group, and a comparative group.
[0133] The demineralization and remineralization experimental procedures were as follows: all enamel samples were immersed in a demineralization solution (50 mmol / L acetic acid, 2.2 mmol / L potassium dihydrogen phosphate solution, 2.2 mmol / L calcium chloride dihydrate solution, 0.5 mol / L sodium bicarbonate solution, pH 4.5), placed in a 37°C shaker at 100 rpm for demineralization for 72 h, and rinsed with deionized water to form artificial caries.
[0134] The artificially demineralized enamel samples were soaked in the mineralization material solution (concentration of 10 mg / mL) prepared by each group for 20 minutes, rinsed with deionized water, and soaked in an acidic buffer (50 mmol / L acetic acid, 2.25 mmol / L calcium chloride dihydrate solution, 0.5 mol / L sodium bicarbonate solution, 1.5 mmol / L potassium dihydrogen phosphate solution, 130 mmol / L potassium chloride solution, pH 5.0) for 30 minutes, rinsed with deionized water, and dried with filter paper. Finally, they were soaked in a neutral buffer (20 mmol / L HEPES buffer, 2.25 mmol / L calcium chloride dihydrate, 1.5 mmol / L potassium dihydrogen phosphate solution, 130 mmol / L sodium chloride solution, pH 7.0) for 10 minutes, rinsed with deionized water, and dried with filter paper. Repeat 6 times a day for 10 days, and spend the rest of the time in a neutral buffer overnight, and the reagents were changed every day. Remineralization of artificial caries.
[0135] The remineralized enamel samples were embedded and cut longitudinally into thin slices along the center of the fenestration area of the enamel samples under a steady water flow. The slices were 110 μm and stained with 0.1 mmol / L rhodamine B fluorescent dye for 1 h. The excess dye was rinsed with distilled water, dried and sealed with glycerol, and placed under a laser scanning confocal microscope. The samples were scanned at an excitation wavelength of 529 nm and the penetration of rhodamine B was observed under a 10x microscope. The scanned images were processed and analyzed using Image J vl.8.0 software and expressed as total fluorescence. Laser confocal microscopy is an advanced method for observing the demineralization and remineralization of tooth hard tissues. The total fluorescence of the carious area was measured by laser confocal microscopy to understand the demineralization and remineralization of the specimens. Enamel itself cannot fluoresce and needs to be stained with dyes such as rhodamine B. It can emit fluorescence after being irradiated by a laser confocal microscope, and then quantitatively analyzed using Image J software. Fluorescent dye molecules can penetrate into the micropores of demineralized enamel, and the demineralization degree of the demineralized area is proportional to the total fluorescence amount.
[0136] The results are shown in Table 1. The results show that the crystals generated by the remineralization of the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared in the embodiment of the present invention reduce the amount of fluorescent dye entering the micropores of the demineralized enamel of the tooth tissue, reduce the degree of caries, and have a remineralization effect. At the same time, it also further illustrates that the embodiment of the present invention has the effect of promoting the remineralization of tooth enamel, thereby achieving the effect of preventing caries.
[0137] Table 1 Effects of Examples and Comparative Examples on Enamel Remineralization
[0138]
[0139] Further, all the enamel blocks were placed under a Vickers hardness tester before demineralization, after demineralization and after the remineralization experiment, and the Vickers hardness (VHN) was measured. The hardness of artificial caries after remineralization was analyzed by the embodiments and comparative examples. The test results are shown in Table 2 below. The results show that the change in dentin microhardness is directly related to its mineral content, and the Vickers hardness of enamel decreases significantly after demineralization. The Vickers hardness of the enamel block after remineralization in the embodiment of the present invention is greatly improved compared with that after demineralization, indicating that compared with before demineralization, the Vickers hardness value can be better improved after treatment in the embodiment, and the degree of enamel demineralization can be reduced.
[0140] Table 2 Vickers hardness of tooth enamel before and after remineralization of examples and comparative examples
[0141]
[0142] Verification Example 2
[0143] The toothpastes prepared in the examples and comparative examples were taken to study their repairing effects on enamel demineralization chalky spots. The specific steps were as follows: 200 subjects were randomly divided into 10 groups after informed consent, namely a control group (using ordinary toothpaste not containing hydroxyapatite), an example group and a comparative example group (n=20 in each group). The subjects cleaned their teeth with the example and comparative example toothpaste every morning and evening for half a year.
[0144] The enamel demineralization index (EDI) is the main indicator reflecting the degree of enamel demineralization, which is measured as follows: the EDI value is calculated based on whether there are chalky spots on the surfaces of the 8 upper teeth. The tooth surface is divided into four areas: gingival, jaw, mesial and distal, with the crown as the center. The degree of demineralization is divided into four levels, where the absence of chalky spots on the enamel surface is recorded as 0 degree, enamel surface spots <50% is 1 degree, 100%> enamel surface spots>50% is 2 degrees, and surface spots that fill the area or have cavities are 3 degrees. The EDI value = the sum of the demineralization scores of each part of the observed tooth accounted for the number of areas of the observed tooth.
[0145] The test results are shown in Table 3. The results show that the EDI value of the toothpaste prepared using the embodiment of the present invention is significantly lower than that of each control group, indicating that the toothpaste prepared in the embodiment can effectively inhibit demineralization when applied to subjects with enamel demineralization chalky spots.
[0146] Table 3 Comparison of enamel demineralization index (EDI) of subjects in the embodiment and the comparative example
[0147]
[0148]
[0149] Furthermore, the plaque index of each group of subjects was tested: after the tooth surface was dried, the amount of plaque on the tooth surface near the gingival margin was directly observed with the naked eye in combination with probing. 0 points means no plaque near the gingival margin, 1 point means plaque can only be seen after the probe is scratched, 2 points means moderate plaque on the gingival margin or tooth surface, and 3 points means a large amount of plaque in the gingival sulcus or gingival margin area and tooth surface.
[0150] The test results are shown in Table 4. The results show that after half a year of treatment with the toothpaste prepared in the embodiment of the present invention, the plaque index of the subjects was significantly lower than that of the control group, indicating that the toothpaste prepared in the embodiment is beneficial for the subjects to better control plaque, which may be because the preparation can inhibit the adhesion of oral bacteria to hydroxyapatite.
[0151] Table 4 Comparison of plaque index values of subjects in the examples and comparative examples
[0152]
[0153]
[0154] It can be clearly seen from the above that the toothpaste prepared by the method of the present invention is significantly better than the comparative examples in terms of enamel mineralization, enamel hardness improvement, enamel demineralization improvement and dental plaque inhibition. The main reason is that, since silk fibroin is neutral, it can be moderately degraded into smaller molecular silk fibroin oligopeptides under neutral conditions by using neutral protease hydrolysis, exposing more enzyme cleavage sites, and preparing for subsequent β-glucanase hydrolysis. In Comparative Example 1, silk fibroin was directly hydrolyzed by β-glucanase without neutral protease hydrolysis, and the order of silk fibroin protease hydrolysis was changed in Comparative Example 2, both of which resulted in a lack of β-glucan cleavage sites on the surface of silk fibroin, making it difficult to hydrolyze to obtain active small molecule oligopeptides, which in turn resulted in a significant reduction in the performance of the toothpaste finally obtained.
[0155] In comparative example 3, the mineralized material prepared by silk fibroin without alkaline hydrolysis is used to make toothpaste, and the oligopeptides in silk fibroin with a larger molecular weight cannot be fully and thoroughly degraded into silk fibroin oligopeptides; in comparative example 4, the mineralized material prepared by silk fibroin first undergoes alkaline hydrolysis and then enzymatic hydrolysis to make toothpaste, and alkaline hydrolysis causes serious denaturation of silk fibroin, and the enzyme cleavage site is wrapped inside the protein, which is difficult to be degraded by biological enzymes; in comparative example 5, the silk fibroin is not subjected to oxidative degradation treatment, and the oligopeptides in silk fibroin with a larger molecular weight cannot be fully and thoroughly degraded into silk fibroin oligopeptides, and it is difficult to mineralize with hydroxyapatite later; although comparative example 6 is subjected to oxidative degradation treatment, it is carried out before enzymatic hydrolysis and alkaline hydrolysis, resulting in serious protein chelation and folding after oxidative degradation of silk fibroin, and the enzyme cleavage site is wrapped inside the protein, which is difficult to be degraded by biological enzymes. Therefore, the toothpaste prepared according to comparative examples 3-6 is also far inferior to the present invention.
[0156] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a hydroxyapatite-silk fibroin oligopeptide mineralized material, characterized in that: The steps include: (1) preparing a silk fibroin solution from silkworm cocoons, and adjusting the concentration of the silk fibroin to 10-100 mg / mL; (2) adding neutral protease for the first enzymatic hydrolysis; then adding β-glucanase for the second enzymatic hydrolysis; (3) adding NaOH to adjust the pH to alkaline, performing alkaline hydrolysis under shaking conditions, and then adjusting the pH to neutral; (4) adding an oxidant to carry out an oxidative degradation reaction under stirring; then adding a reducing agent to continue the stirring reaction; (5) ultrafiltration of the reaction product to obtain a silk fibroin oligopeptide solution, and freeze-drying to obtain a silk fibroin oligopeptide; (6) The silk fibroin oligopeptide obtained in step (5) is mixed with hydroxyapatite and dissolved in a saturated calcium nitrate solution, and a sodium phosphate solution is added dropwise under stirring to carry out a mineralization reaction; after the mineralization reaction is completed, the pH is adjusted to neutral, the precipitate is collected by centrifugation, and the precipitate is dried and ultrafinely ground and sieved to obtain the product.
2. The preparation method according to claim 1, characterized in that: The temperature of the first enzymatic hydrolysis in step (2) is 30-50° C. and the time is 30-90 min.
3. The preparation method according to claim 1, characterized in that: The temperature of the second enzymatic hydrolysis in step (2) is 40-60° C. and the time is 10-60 min.
4. The preparation method according to claim 1, characterized in that: In step (3), the pH is adjusted to 8.0-11.
0.
5. The preparation method according to claim 1, characterized in that: The temperature of the oxidative degradation reaction in step (4) is 30-60° C. and the time is 1-20 min.
6. The preparation method according to claim 1, characterized in that: The stirring reaction in step (4) is carried out at a temperature of 30-60° C. and for a time of 10-60 min.
7. The preparation method according to claim 1, characterized in that: The temperature of the mineralization reaction in step (6) is 30-40°C.
8. The hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the hydroxyapatite-silk fibroin oligopeptide mineralized material prepared according to the preparation method according to any one of claims 1 to 7 in the preparation of toothpaste.
10. A toothpaste, characterized in that: The invention comprises a hydroxyapatite-silk fibroin oligopeptide mineralized material prepared by the preparation method according to any one of claims 1 to 7, and auxiliary materials.
Citation Information
Patent Citations
Preparation method of silk fibroin peptide with bacteriostatic activity
CN102965423A
Anthocyanin sustained-release microcapsule, preparation method thereof and skin care product
CN113318049A